Os acordos setoriais previstos na Lei Federal n. 12.305/2010 (Política Nacional de Resíduos Sólidos PNRS): desafios jurídicos para a implementação da logística reversa no Brasil - Soler, Fabricio Dorado (2014)
National Solid Waste Policy (NSWP), laid down by Federal Law n. 12,305/2010 and further elaborated by Federal Decree n. 7.404/2010, provides for important instruments to ensure the environmentally sound waste management in Brazil, among which is to highlight the shared responsibility for the lifecycle of products. Shared responsibility for the lifecycle of products, as defined by the NSWP, comprises a set of individualised albeit chained duties imposed upon manufacturers, importers, distributors and sellers as well as consumers and the waste management services providers in order to minimise the amount of waste generated and reduce the impacts on human health and environmental quality resulting from the lifecycle of products. With a view to implementing the shared responsibility for the lifecycle of products, the NSWP has established inter alia duties to take back and manage recycle, recover and/or dispose of end-of-life products (post-consumer waste) in an environmentally sound manner. Taken together, these two duties are known as reverse logistics , which is legally defined by the NSWP as an economic-and-social-development tool consisting of a set of actions, procedures and means aimed at having waste collected and then returned to the private, entrepreneurial sector for either further use/processing into productive lifecycles or other type of environmentally-sound waste disposal. Sectoral agreements constitute one of the ways reverse logistics may be structured and implemented. They are defined as a contractual act entered into by the government (public power) and manufactures, importers, distributors and/or sellers so as to implement the shared responsibility for the lifecycle of products. Both the NSWP and Federal Decree n. 7.404/2010 seem to favour sectoral agreements despite the legal possibility of resorting to regulations and commitment agreements (termo de compromisso). Federal Decree n. 7.404/2010 prescribes the minimum requirements for drafting and proposing sectoral agreements, which shall be analysed by the Ministry of Environment, made open to public consultation and then sent to the Guidance Committee for the Implementation of Reverse Logistics Systems (Cori). Such a Committee may accept the proposal, ask for amendments or determine the archiving thereof when no consensus has been reached during the negotiations. The present study aims at tackling the main legal challenges underpinning the structuring and implementation of reverse logistics systems via sectoral agreements. Moreover, the relevance of the study is associated with the demonstration of possible risk to derail the structuring and implementation of reverse logistics system by the business sector. This is because, by failing to obtain consent to enter into sectoral agreement, the Government may edit rules unilaterally, without, therefore, consider the isonomic, proportionate and reasonable manner its own powers under the shared responsibility for the lifecycle of products, as a holder of public urban sanitation and solid waste management